Is nab-paclitaxel better than conventional taxanes as neoadjuvant therapy for breast cancer? A meta-analysis. Issue 8 (August 2020) - Li, Yong; Lu, Xiaoju; Lin, Qimou; Li, Weiwen
Objective: This study compared the efficacy and safety of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) with conventional taxanes as neoadjuvant chemotherapy for breast cancer. Methods: We searched the literature using PubMed, the Cochrane Library, and Web of Science from their inception to December 15, 2019 based on predetermined inclusion and exclusion criteria. The relevant studies compared pathologic complete response (pCR) and adverse event rates. Results: The meta-analysis included five studies and 2335 patients. Compared with conventional taxanes, neoadjuvant chemotherapy with nab-paclitaxel was associated with a higher pCR rate (odds ratio [OR] = 1.39, 95% confidence interval [CI] = 1.16–1.67), especially among patients with triple-negative breast cancer or Ki67 indices of >20%. Pooled outcomes also revealed better event-free survival in the nab-paclitaxel group (hazard ratio = 0.69, 95% CI = 0.57–0.85). However, all-grade (OR = 2.17, 95% CI = 1.38–3.40) and grade ≥3 peripheral sensory neuropathy (OR = 3.92, 95% CI = 2.44–6.28) were more frequent in the nab-paclitaxel group. Conclusions: This meta-analysis implied that nab-paclitaxel more effectively improved pCR than conventional taxanes. Nab-paclitaxel may have greater benefits in patients with triple-negative breast cancer. However, additional attention is required for the early diagnosis and management of peripheral sensory neuropathy.